Student engagement in responding activities: Insights and impacts on guidance and counseling practices - Pohan, Rizky Andana; Daharnis, Daharnis; Bentri, Alwen (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2024)
Purpose - Perception is one of the variables included in individual characteristics that affect response activities in learning. The purpose of this study is to analyse the description of students' perceptions of responding activities in learning.Method - Descriptive quantitative research method with a population of 480 students and a sample of 218 students with proportional random sampling technique representing all classes. Data analysis techniques used with percentages.Result - The results showed that student perceptions of responding activities on average were in the positive category, as well as for the two indicators, namely perceptions of the purpose and benefits of responding activities, each also in the positive category.Implication – Based on the results of research on students' perceptions, it can be used as a basis in the preparation of counseling programmes based on needs analysis to improve responding activities in learning. Furthermore, in the implementation stage of the programme, students' perceptions can be improved with various BK services, including basic services with various components such as classical guidance, group guidance and information media management regarding the purpose and benefits of responding.Originality/Value – Novelty in this study is related to the description of student perceptions in responding activities that have never been studied by previous researchers in an analytical descriptive manner as well as its implementation of counseling services in schools.***Tujuan - Persepsi merupakan salah satu variabel yang termasuk dalam karakteristik individu yang mempengaruhi aktivitas merespon dalam pembelajaran. Tujuan dari penelitian ini adalah untuk menganalisis gambaran persepsi mahasiswa terhadap aktivitas merespon dalam pembelajaran.Metode - Metode penelitian deskriptif kuantitatif dengan populasi 480 siswa dan sampel 218 siswa dengan teknik proporsional random sampling yang mewakili semua kelas. Teknik analisis data yang digunakan dengan persentase.Hasil - Hasil penelitian menunjukkan bahwa persepsi mahasiswa terhadap kegiatan merespon rata-rata berada pada kategori positif, begitu juga untuk kedua indikator yaitu persepsi terhadap tujuan dan manfaat kegiatan merespon masing-masing juga berada pada kategori positif.Implikasi - Berdasarkan hasil penelitian mengenai persepsi siswa, dapat dijadikan dasar dalam penyusunan program BK berdasarkan analisis kebutuhan untuk meningkatkan kegiatan menanggapi dalam pembelajaran. Selanjutnya pada tahap implementasi program, persepsi siswa dapat ditingkatkan dengan berbagai layanan BK, termasuk layanan dasar dengan berbagai komponennya seperti bimbingan klasikal, bimbingan kelompok dan pengelolaan media informasi mengenai tujuan dan manfaat merespon.Orisinalitas/Nilai - Kebaruan dalam penelitian ini terkait dengan gambaran persepsi siswa dalam kegiatan responding yang belum pernah diteliti oleh peneliti sebelumnya secara deskriptif analitis serta implementasinya terhadap layanan BK di sekolah.